The Efficacy and Safety of Interventional Cardiac Catheterization in Children during Early Post Operative Period after Cardiac Surgery - Muhammed A. Arfi; Jameel A. Al-Ata; Arif H. Ishtiaq; Salem Deraz; Zaher F. Zaher; Amjad A. Kouatli (Journal of King Abdulaziz University: Medical Sciences, 2023)
Interventional cardiac catheterization in children is important and generally considered as a safe tool in the management of congenital heart diseases. Evolution over time has lead to its extended application in post-operative patients after cardiac surgery. This report presents an experience of forty-three procedures conducted on thirty-five children during an immediate post-operative period after cardiac surgery. Thirty patients survived (five patients died due to non-cardiac causes) who underwent 37 procedures. Twenty-seven patients (34 procedures) were successfully weaned off the ventilator, while three patients (3 procedures) were weaned off the cardiopulmonary support. Out of the 37 procedures, twenty-seven proved effective and nine proved partially effective, as additional surgical interventions such as plication of diaphragm and/or tracheostomy were also required. All, but one procedure rated successful. The stenoses/obstructions in synthetic conduits or natural vasculatures were dilated successfully; residual shunts were either effectively occluded, or minimized to an insignificant level. Balloon dilatation of a blocked Blalock Taussig Shunt in one patient was unsuccessful and a re-insertion of another shunt was performed. It has concluded that under controlled conditions, transcatheter intervention during immediate post-operative period is safe and effective. Surgical and anesthesia backup should be readily available in case a situation arises.